Nurturing the Culture of Dialogue: A Macedonian Experience - Gjorgjevski, Gjoko (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
Abstract The aim of this paper is to describe the relations between the religious communities in the Republic of North Macedonia. This paper will examine the history of each of the most numerous traditional religious communities in the country, the history of the dialogue between them and its present situation, the communication and mutual influences, as well as the attempts to overcome disagreements and misunderstandings. It is an overview of the most important activities of the dialogues and challenges in relation to the events and changes in the country.